Educators Strategies: Overcoming Students’ Speaking Difficulties - Rezeki, Ria (Journal of Education Review Provision, 2022)
This research aims to assess the teaching methods applied by English teacher at SMA Negeri 1 Selayar to overcome the barriers to speaking English for their students in EFL context. Using a descriptive qualitative research approach, the study concerns the incorporation of role-play, simulations, group discussion, vocabulary games and positive re-enforcement to foster the development of the students’ speaking skills. Questionnaires, observations and document reviews were designed and semi structured interviews were carried out and themes were analysed. The findings shown above prove that using the role-play and simulation members improve learners’ confidence and fluency in the actual contexts. Group meetings help learners to build up interactional proficiency since they become more free and organic with others as compared to performances. It has been established that vocabulary games are effecting in improving the students’ ability to recall and use the words as well as in motivating the students through positive reinforcement. The main study emphasizes the realistic utility of these approaches and their evidence base in instructional theories as well as their effectiveness in improving language learning achievements in EFL contexts. To the best of current knowledge, the present investigation adds to the existing literature by offering qualitative evidence in support of the means and ends of interactive and student-centered methods of language instruction.